Herbaceous Alfalfa plant as a multipurpose crop and predominant forage specie in Pakistan - Latif, Ammara; Sun, Ying; Noman, Ali (Frontiers in Sustainable Food Systems, 2023)
Fodder crops play an important role in agriculture as they deliver food for animals, which is eventually converted to food for humans. All over the world, Alfalfa has had utmost importance for a few decades, not only as a fodder crop due to having high nutritional value for dairy farming but also being positively involved in many health-related and environmental affairs. Medicinally, it helps in controlling diseases such as arthritis, cholesterol, anemia, and cardio-related illnesses. Furthermore, like other cereal crops (wheat, rice, corn, etc.), it could also be a great source of several healthy nutrients for humans when the proper quantity is added to daily meals. However, unlike other nations of the world such as America, China, and India, Pakistan does not utilize it directly in human meals. This crop also has eco-friendly behavior since it controls soil erosion by binding the soil particles together and makes atmospheric nitrogen available to the plants by fixing it in the soil. Other uses include its role in water purification, improved pollination, and most importantly, its tolerance against water, salt, and temperature stress, making its position even stronger in arid and semi-arid areas. This review will draw researchers' attention to its multiple uses other than fodder crop and most importantly, its nutritional availability at a very low cost, which could prove nothing short of a miracle for the economy if properly mediated.